Firepower : How the NRA Turned Gun Owners into a Political Force - Lacombe, Matthew J. (Book collections on Project MUSE., 2021)
"Firepower explores how the NRA gradually transformed itself from a relatively small organization with close ties to the federal government and a mission dedicated to marksmanship, competitive shooting, and military preparedness to what it is today: A political juggernaut that pushes a right-wing, populist world view and enjoys a prominent position in the Republican Party coalition. As Lacombe shows, NRA members and supporters participate in politics at unusually high rates, and have for decades, successful opposing gun regulations despite the shockingly high rates of gun violence in the U.S. relative to other countries and deep, durable public support for stricter rules on gun ownership. Understanding how and why this came to be can not only teach us about the evolution of one of the most influential interest groups operating today, but can also shed light on how interest groups more generally can marshal the political behavior of their supporters over time in order to build and exercise power. Most of the work done on interest group influence focuses on behind-the-scenes tactics such as lobbying and campaign support. Yet this is not the source of the NRA's power. Instead, it is the group's ability to shape the political outlooks of its supporters on behalf of its agenda. The NRA has done this by creating a gun owner culture and social identity that mobilizes individuals to engage in various forms of political participation, and by linking gun rights to other political issues, generating a broader political ideology. Drawing on almost a century of archival data, Lacombe illuminates the NRA's identity- and ideology-building efforts in fine-grained, historical detail, ultimately showing how the group came to align with the Republican Party and considering the causes and consequences of the NRA's increasingly deep relationship with the GOP in the age of Donald Trump"--